Conceptualising sustainable communication at the intersection of ethics, reflexivity and critique - Ditlevsen, Marianne Grove; Johansen, Trine Susanne (Communication & Language at Work, 2024)
This paper addresses sustainability as an overarching principle for strategic communication reflecting a changing organisation-society interface where organisations are seen as political actors with citizenship obligations. Such a change calls for a responsibilisation of communication and for communication, itself, to be sustainable. Based on this, the paper sets out to present the theoretical concept of sustainable communication as a foundation for making communication responsible. Sustainable communication refers to communication practices which benefit not only organisations, but also people and society at large. An integrated framework for sustainable communication is developed based on three mindsets which are considered the central foundations, i.e. the ethical, the reflexive and the critical mindset, respectively. Taken together, the three mindsets lay the foundation for explicating the communicative implications and consequences associated with the changing roles of organisations in society by highlighting central relational aspects. Ethics orients attention towards how organisations address the other, i.e. organisational stakeholders, in the communication process. Reflexivity connects to the active recognition and investigation of organisational assumptions regarding the other and the organisation-other relationships. And the critical approach directs awareness towards the inherent, frequently implicit, or invisible, power dimensions characteristic of organisations-other relationships. Further, implications for theory, education and practice are discussed. Moreover, a process and dialogue tool in the form of a cobweb is offered as an inspiration for addressing sustainable communication issues in practice. Finally, it is suggested that sustainability has the potential to develop into a third turn to accompany the communicative and the strategic turns that have already taken place within communication scholarship.